Effect of citral on mouse hepatic cytochrome P450 enzymes - Huaqiao Tang; Nana Long; Min Dai; Lin Lin; Jianlong Li; Fenghui Sun; Lijuan Guo (Taylor & Francis Group, 2018)
Context: Citral is used as a potential natural treatment for various infectious diseases. Objective: To examine the effect of citral on the mRNA expression and activities of cytochrome P450 (CYP450) enzymes and establish the relationship between citral-induced liver injury and oxidative stress. Materials and methods: ICR mice were randomly divided into citral (20, 200, and 2000 mg/kglow), Tween-80, and control groups (0.9% saline), 10 mice in each group. The citral-treated groups were intragastrically administered citral for 3 d, control groups treated with 0.5% Tween-80 and 0.9% saline in the same way. Liver injury and CYP450 enzymes were analyzed by analyzing the histopathological changes and the changes of related enzymes. Results: Citral treatment (2000 mg/kg) for 3 d increased serum glutamic pyruvic transaminase and glutamic oxaloacetic transaminase levels, as well as glutathione, gydroxyl radicals, malonaldehyde and total superoxide dismutase contents, but decreased the content of total antioxidant capacity. In doses of 20 and 200 mg/kg groups mice, the contents of NO were decreased significantly and other changes were similar to the 2000 mg/kg group mice, but the liver damage was most severe in the 2000 mg/kg group. Citral induced the mRNA expression and activities of CYP450 1A2, 2D22, and 2E1 in the liver of mice at doses of 20 and 200 mg/kg. There were no changes in testing indexes in Tween-80 treated group mice. Due to its toxic effects, the CYP induction effect of citral negatively correlated with its dose. Although the mRNA expression of CYP450 3A11 was induced by citral, its activity was not affected by low and moderate doses of citral. CYP450 3A11 activity was significantly decreased by high-dose citral. Conclusions: Citral is hepatotoxic and induced oxidative stress in higher dose, which has a negative effect on CYP450 enzymes. These data suggest caution needs to be taken in order to avoid citral-drug interactions in human beings.